Seismic Behavior of Flat Slab for Optimum Location of Bracings. Issue 1 (1st March 2022) - Pooja, H S; Shashikumar, N V; Narayan, G; Narendra, B K
Abstract: As increasing population necessity of the land required to build a structures is keep on decreasing so that high rise structures are everywhere. Use of flat slab in high rise structure has many advantages compared to RC conventional slab system. To increase the lateral resistivity of the flat slab building, diagonal type buckling restrained braces are provided at the corners. The main objective is to know about the Seismic behavior of flat slab with BRB for different re-entrant corner irregularities(Plus, T, L), using nonlinear time history analysis with help of ETABS software. 20storey flat slab drop panel building with BRB is modelled and analyzed in zone III. Comparing the different re-entrant irregularity buildings with and without bracings. Plus shape flat slab with bracing building shows better performance compared to all other models with respects to various parameters such as lateral displacement. Storey drift, storey stiffness, base shear and time period.